Surveillance on screen : monitoring contemporary films and television programs - Lefait, Sebastien, 1976- (Scarecrow Press, Inc., 2013)
Drawing on the rapidly developing field of surveillance studies, this book examines television shows and films-including Lost, Survivor, Minority Report, Enemy of the State, and Nineteen Eighty-Four-that shape our experience of surveillance, both as watchers and as those being watched.